2003
DOI: 10.1002/pi.1040
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of unsaturated polyester resin synthesis. Part I: modelling and simulation of reactant sequence length distributions in stepwise polymerization

Abstract: The quantification of the relationship between physical properties of polymeric products and the sequence distribution of comonomer units in a polymer chain is not an easy task. In this work, detailed consideration is given to the sequence lengths and sequence length distributions to be expected in unsaturated polyesters formed by the reaction of maleic anhydride, phthalic anhydride and a diol, a reaction which gives rise to the low molecular weight precursors used in unsaturated polyester resins. Monte Carlo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Based on the selective acid hydrolysis [13] of polyesterepolyurethanes and using size-exclusion chromatography (SEC) as a subsequent analytical technique, it is possible to measure the SLD of this family of polymers [14,15]. Sequence length distributions were also studied in the production of unsaturated polyesters formed by the reaction of maleic anhydride, phthalic anhydride and a diol [16]. Recently, the presence of microphase separation between hard microdomains and a soft segment matrix for polyurethaneeurea copolymers based on ethyleneebutylene soft segment was experimentally established [17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the selective acid hydrolysis [13] of polyesterepolyurethanes and using size-exclusion chromatography (SEC) as a subsequent analytical technique, it is possible to measure the SLD of this family of polymers [14,15]. Sequence length distributions were also studied in the production of unsaturated polyesters formed by the reaction of maleic anhydride, phthalic anhydride and a diol [16]. Recently, the presence of microphase separation between hard microdomains and a soft segment matrix for polyurethaneeurea copolymers based on ethyleneebutylene soft segment was experimentally established [17].…”
Section: Introductionmentioning
confidence: 99%
“…transesterification of polyesters. [1,3,4] This ''reshuffling'' of the chain-length distribution of linear polymer(s) ideally results in the MWD approaching the most probable (Schulz-Flory) distribution. [1,2,5] Free radical ring-opening polymerizations have received considerable attention as a means of reducing the level of shrinkage normally associated with free radical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that interchange reactions analogous to those in polyester [3,4,17] and polyamide [18] systems may occur in case of the eight-membered disulfide monomer, 2-methyl-7-methylene-1,5-dithiacyclooctane (MDTO). [13] The idea of these interchange reactions was put forward based on the finding of bimodal MWDs, which were speculated to originate from backbiting via addition of the propagating sulfur radical species to one of the double bonds on the polymer backbone, with subsequent b-fragmentation (i.e.…”
Section: Introductionmentioning
confidence: 99%